MODEL ROTATING CYLINDER ELEKTRODE UNTUK MENENTUKAN KEPERLUAN RAPAT ARUS PROTEKSI KATODIK - Utami, Isni (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Effect of fluids flow rate onto necessity of current density cathodic protection which characterized using Rotating cylinder electrode (RCE) model has been researched on an electrochemistry manner. This research was done to AISI 1018 steel as the electrode spinning cylinder-shaped inside aerated dissolvable NaCl 3.5%. using variation spinning rate 0-2000rpm and 25-75 0C temperature. Current density cathodice protection necessity determined from the steel interface potential -800mV with reference anode Ag/AgCl. Experiment result shows as the increasing of electrode rate, cathode protection current density needs increased due to diffusion layer tare faction and also because corrosion potential become more positive. Higher temperature would increasing cathode protection current density needs and makes corrosion potential more negative. Oxygen activation energy value to be diffused onto electrode surface support the corrodibility AISI 1018 toward temperature increment, because cathode reaction controlled by transfer mass of dissolved oxygen. With un-dimensioned number analysis and data experiment calculation, empiric formula which is functional relation between electrode rate/fluids flow rate characterized as turbulence flow toward cathodic protection current density is mentioned below: iPRCE = 0,0841 0,6539 0,4976